Influence of welding parameter on mechanical properties and microstructural features of resistance spot welded dual phase steel sheets joint. (2020) - Sivaraj, P.; Seeman, M.; Kanagarajan, D.; Seetharaman, R.
Abstract: Similar joints of DP600 (Dual Phase) steel in lap joint design were fabricated using resistance spot welding (RSW) method. The most influencing welding parameters of resistance spot welding are welding current, welding time and electrode force. The mechanical properties evaluated through shear fracture test in a universal tensile testing machine. Hardness measurement carried out different regions of the weldment. The fusion zone microstructure was analyzed through the optical microscopy. In this study mainly focused on varying the current level and remains constant other processes parameters while fabricating lap joints of the RSW. From the results observed that while increasing current range the shear strength values have increased up to certain limit then it gets degrades. It also found that most of the failures in the nearer region of the fusion zone (FZ). This mainly due to straining distortion of Crystal lattice it weaken the nearer region of the fusion zone.